Discourse of concern in addressing the educational needs of Malay children in foster care - Mohd Jan, Jariah; Talif, Rosli; Mohd Zaid, Ainun Rozana @ Ainun; Suffian Sahuri, Sakina Sahuri; Omar, Haslina (2014)
Children in foster care, generally, perform poorly in school (Watson & Kabler, 2012; Emerson & Lovitt, 2003; Zeitlin, Weinberg & Kimm, 2003). There is a notion of uncertainty over the question of who has primary responsibility over the academic progress of foster children. Foster children are among economically disadvantaged children who face social, emotional and psychological concerns that can affect their academic performance and hence, their futures, as once they are discharged and no longer in the care of the state, their future prospects will be largely based on their school performance. Previous studies have shown that foster children avoid social interactions with peers in order to keep their foster status hidden and may choose to blame themselves for their poor academic performance (Watson & Kabler, 2012; Zeitlin, Weinberg & Kimm, 2003). Further, there is limited communication and exchange of information between foster children, foster caregivers and the teachers in the school that the children attend. Majority of teachers and other school personnel are acquainted in dealing with normal children. Some teachers are specialized at dealing with children who have been identified with special needs like those with dyslexia, human communication problems and physical disability, while there are those trained to deal with gifted children. However, foster children are treated as ‘normal’ children because only «few teachers are knowledgeable about the extensive problems these children have while they are in school» (Emerson and Lovitt, 2003:199). As such, addressing the educational needs of foster children have not been directly dealt with which may be due to the lack of professional practices in this area of concern. This study looks at the voices of concern emerging from the social and professional practices involved in addressing the educational needs of Malay children in foster care. This study draws on semi-structured interviews with teachers, counselors, assistant principal and principal to better understand how they can help these children perform in school. The extensive narratives of teachers’ educational experiences by way of teaching, counselling, socializing, managing the children’s behavior and involvement in sporting and extra-curricular activities were recorded to learn what they regard as concerns hindering the children’s educational success. Content analysis is used in this qualitative approach to describe the concern voiced by the teachers about the foster care children. The narratives elicited from the interviews are analyzed based on the various categories of concern as elucidated by Rhee et al. (2013). This study has found that the discursive concern vary according to the levels of commitment and empathy. %ere are strong indications that in establishing primary responsibility for educational matters, there should be no disregard of others in dealing with the concerns and special needs of these foster care children.